Eksplorasi Authentic Assesment Dalam Moderasi Beragama Di SD Al-Qur’an Ummul Quro Pangaporan Plakpak Pegantenan Pamekasan - Syafiq Fahmi, Ach; Permatasari, Intan Dwi; Jannah, Faridatul; Mukhid, Abd. (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
This research aims to explore Authentic Assessment in religious moderation at SD Al-Qur'an Ummul Quro Pangaporan Plakpak Pegantenan Pamekasan. This research uses a qualitative research method with a descriptive approach. The data collection technique uses observation, interviews and questionnaires. The results of this research explain that authentic assessment in religious moderation at Ummul Quro Al-Qur'an Elementary School has been carried out well in accordance with the plan agreed at the beginning of the semester by each teacher. This authentic assessment is carried out by assessing 3 aspects of students, namely the cognitive aspect ( knowledge), Affective (attitude), and Psychomotor (Skills). These three aspects of assessment produce 4 categories of students after the end of the learning activities/at the end of the semester. The 4 categories in question are: 1) Science Star, 2) Religious Star, 3) Creativity Star, and 4) Favorite Star. The implementation of Authentic Assessment in religious moderation at Ummul Quro Al-Qur'an Elementary School has supporting and inhibiting factors. Among the supporting factors are the Full Day School education system implemented at Al-Qur'an Elementary School and the many religious activities, such as congregational Dhuha, Dhuhur and Asar prayers, reciting the Koran together, etc. Meanwhile, the inhibiting factor arises from naughty students, because the presence of naughty students can hinder assessment and influence other students